(untitled) (The Conference Hub, 2025)
This article examines the evolution of global financial centers (GFCs) using the Global Financial Centers Index (GFCI) as a framework for analysis. It proposes a life-cycle model that captures the rise, maturity, and possible decline of centers and evaluates the key factors shaping their competitiveness. By analyzing trends in major hubs such as New York, London, Singapore, and Shanghai, the study identifies human capital, regulatory quality, technological innovation, and global reputation as decisive drivers of long-term success. The findings highlight how the GFCI reflects structural transformations in international finance and serves as a predictive tool for policymakers and market participants.